HMGB1: A pleiotropic activity. (24th November 2020) - Colavita, Laura; Ciprandi, Giorgio; Salpietro, Annamaria; Cuppari, Caterina
Abstract: High‐mobility group box 1 (HMGB1) is a nuclear protein involved in DNA replication, transcription, recombination, and repair. In the extracellular space, the HMGB1 plays an essential role in the onset and perpetuation of inflammation, belonging to the group of damage‐associated molecular pattern (DAMP) molecules, also called alarmins. For this, HMGB1 has been studied in several acute and chronic inflammatory diseases as an early biomarker of inflammation. An increased concentration of HMGB1 has been detected in serum, as the expression of systemic inflammation, and in specific samples (such as stool, synovial fluid, nasal lavage fluid, sputum, and cerebrospinal fluid), as the expression of local production, in several infectious and/or inflammatory diseases. These data are particularly important because they open new futuristic possibilities for target therapies, potentially also for the COVID‐19 treatment.